Shaping Organizational Communication: The Impact of AI and Language through Weick's Sensemaking Theory - Yaroglu, Aslihan Canbul (SAGE PUBLICATIONS INC, 2025)
Organizational communication plays a critical role in shaping the success of modern businesses. In today's rapidly digitalizing environment, organizations are becoming aware of the changes that new technologies create in internal communication. The effectiveness of communication in organizations depends on the correct use of language production and meaning processes. Understanding the complex relationship between language production, organizational communication, and meaning-making is particularly important to grasp the role of artificial intelligence (AI) in these processes. This study integrates Karl Weick's Theory of Meaning with a phenomenological framework to examine how language mediates communication in organizations from a phenomenological perspective. The integration of AI technologies in organizations adds new dimensions to corporate communication strategies, increases the accuracy of language use, and reduces uncertainty. However, this process also requires careful consideration of ethical implications and the dynamics of organizational culture. This study examines in depth the integration of Weick's theories with AI-supported communication tools, highlighting the challenges and opportunities that arise in this context. It explores the potential of AI technologies, especially in areas such as language processing and machine learning, in providing a more effective meaning-making process in corporate communication. Finally, the research highlights the importance of creativity and standardization of meaning, suggesting that with the increasing use of AI to maximize its benefits in organizational communication, a more consistent and effective communication process can be achieved.
Keywords: phenomenology; sensemaking; organizational communication; artificial intelligence; Karl Weick; SOURCE ORIENTATION; TECHNOLOGY; BODY; Business & Economics; Communication